Michael D. McNally, Defend the Sacred: Native American Religious Freedom Beyond the First Amendment - Glassman, Matthew E. (Journal for the study of religion, nature and culture, 2022)
Michael D. McNally, Defend the Sacred: Native American Religious Freedom Beyond the First Amendment (Princeton: Princeton University Press, 2020), 400 pp., $99.95 (hbk), ISBN: 9780691190891.